(untitled) (International Journal of Statistical Sciences, 2024)
Micro-credit has been playing a vital role in developing wetland people’s socio-economic status by facilitating their income-generating activities such as seasonal fish farming, raising ducks and cattle, and floating vegetable gardens. Wetland people’s livelihoods are largely dependent on borrowing micro-credits, but access to formal credits is somewhat intricate for them due to procedural complexity. Therefore, this study aims to explore the potential discriminating factors of formal credits in the wetland region of Bangladesh. This study used data from 1607 micro-credit receiver households that were collected by a research project sponsored by the GARE Program, Ministry of Education, Government of Bangladesh. The discriminant analysis was performed to explore the factors discriminating between formal and informal credit-receiving groups. This study considered three types of factors such as borrower’s individual-level, household-level, and micro-credit related characteristics as the potential factors distinguishing between formal and informal credits. The findings show that micro-credit-related factors such as the number of installments, duration of the loan, and rate of interest are more crucial for affecting formal credit in the wetland peoples of Bangladesh. Most vulnerable groups in the wetland region still struggle to obtain formal credit because of obstacles such as a lower number of installments, lower duration of loans, and high interest rates. The government policy should remove these obstacles to ensure the people’s easy access to formal loans, which would ultimately improve their socio-economic conditions. International Journal of Statistical Sciences, Vol. 24(2), November, 2024, pp 85-96